Markets Versus Monopolies in Education - Coulson, Andrew J. (Education Policy Analysis Archives, 1996)
A common point of contention among educators and economists is the likely effect a free market would have on modern education. Most supporters of public schooling maintain that the field would either be adversely affected by competition and choice, or that the effects would be insubstantial. Conversely, a significant number of critics argue that education, like all other human exchanges, would respond to market incentives with improved performance, increased attention to the needs of families, and greater innovation. Historical evidence is presented indicating that teachers and schools are indeed affected by the financial incentives of the systems in which they operate. In particular, the data show that economic pressures have forced schools in competitive markets to meet the needs of families, through methodological advancements and diversity in curriculum, while centralized bureaucratic systems have generally been coercive and pedagogically stagnant.